Frontiers and Wars - Churchill, Winston S. (Middlesex, England Penguin Books, 1972)
The first four books (abridged) written by Sir Winston Churchill, while serving as a soldier and war correspondent.
Include Maps and Illustrations.
Edited into one volume. His four early books, covering his life as soldier and war correspondent. It is a biography.
Keywords: Armed Forces--Military life -- Great Britain. Army -- British colonies -- Churchill, Winston, 1874-1965 -- South African War (1899-1902) -- Sudan -- India. Army. Malakand Field Force